From Fast Fashion to Thrift: Generation Z’s Sustainable Consumption Behavior in Bandung - Grahadian, Kevin; Widyarini, Maria; Zhukhruffa, Syayu (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study examines the determinants of thrift shopping practices among Generation Z consumers in Bandung, Indonesia, using an extended Theory of Planned Behavior (TPB) framework within the context of sustainable fashion consumption. The research specifically examines how perceived behavioral control, subjective attitudes toward behavior, and influence affect thrift shopping practices. A quantitative approach was employed, using a structured questionnaire distributed to Generation Z individuals with prior thrift-shopping experience. A total of 200 valid responses were collected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and test the proposed structural relationships. The results reveal that environmental awareness, social and cultural influences, and psychological factors have significant positive effects on thrift shopping practices. In contrast, economic considerations, barriers, convenience and accessibility, and emotional–hedonic factors do not show significant effects. Notably, perceived behavioral control shows no significant relationship, suggesting that thrift shopping among Generation Z is driven more by social validation and psychological motivation than by utilitarian control considerations. The model explains approximately 63% of the variance in thrift shopping practices.